Exploring visitors experience, motivations, and transformative experience at a vegan gastronomic festival: The case of Vegan Fam Festival - Pericleous, Katerina; Mina, Anastasia; Christou, Prokopis A. (My University, 2025)
Veganism has evolved from a niche lifestyle into a global sociocultural phenomenon, with over 2.6 million Europeans identifying as vegan in 2023. This growing movement is not only reshaping dietary habits but also influencing business practices, consumer markets, tourism, and academic research. This is reflected in the increasing organization and popularity of vegan-themed festivals that blend gastronomy, sustainability, and transformative experiences. This study explores the visitor experience at the Vegan Fam Festival in Cyprus - an event centered on plant-based gastronomy, environmental awareness, and ethical living. Using a quantitative methodological approach, it investigates visitors’ motivations (n=154), satisfaction, and the potential for behavioral transformation through the festival experience. Results indicate high overall satisfaction, with omnivores reporting slightly higher levels than vegans. A notable percentage of participants also reported that the festival inspired them to adopt more sustainable lifestyle practices. The findings position this specific festival not only as a culinary and cultural event but also as a platform for identity expression, education, and long-term behavioral change. This study contributes to the theoretical understanding of tourist motivation and satisfaction within the underexplored context of vegan tourism. Furthermore, it highlights the potential of vegan festivals to serve as transformational, value-driven tourism experiences within a shifting global food culture - a field that remains relatively new and understudied in tourism and hospitality research.
Keywords: Vegan festivals; Ethical living; Cultural events; Experiential tourism; Plant-based lifestyle; Sustainability